Narratology beyond the human storytelling and animal life - Herman, David 1962- (Oxford University Press, 2018)
To what extent, and in what manner, do storytelling practices accommodate nonhuman subjects and their modalities of experience, and how can contemporary narrative study shed light on interspecies interactions and entanglements? In Narratology beyond the Human, David Herman addresses these questions through a cross-disciplinary approach to post-Darwinian narratives concerned with animals and human-animal relationships. Herman considers the enabling and constraining effects of different narrative media, examining a range of fictional and nonfictional texts disseminated in print, comics and graphic novels, and film. In focusing on techniques such as the use of animal narrators, alternation between human and nonhuman perspectives, the embedding of stories within stories, and others, the book explores how specific strategies for portraying nonhuman agents both emerge from and contribute to broader attitudes toward animal life. Herman argues that existing frameworks for narrative inquiry must be modified to take into account how stories are interwoven with cultural ontologies, or understandings of what sorts of beings populate the world and how they relate to humans. Showing how questions of narrative bear on ideas of species difference and assumptions about animal minds, Narratology beyond the Human underscores our inextricable interconnectedness with other forms of creatural life and suggests that stories can be used to resituate imaginaries of human action in a more-than-human world
Keywords: Mensch; Tiere; Erzähltheorie; Human-animal relationships in literature; Animals and civilization; Animals in literature; Storytelling; Narrative inquiry (Research method); Narration (Rhetoric)